ҚАРАҚАЛПАҚ ЖЫРАЎШЫЛЫҚ ӨНЕРИ ҲӘМ МЕКТЕБИ: ДӘСТАН ДӨРЕТИЎШИЛИК ДӘСТҮРЛЕРИ, САҒАЛАРЫ, ҲӘЗИРГИ ЖАҒДАЙЫ, КЕЛЕШЕК ТӘҒДИРИНИҢ ӘҲМИЙЕТЛИ МӘСЕЛЕЛЕРИ - Аяпов, С.Б.; Эгамқулова, Г.М. (ILIM hám JÁMIYET, 2021)
The article presents historical opinions about the Karakalpak school of dzhirovism, fats and their instrument «kobiz». Moreover, it is studied the issues and problems of the past and present of the dzhirovism, the state of development, its role in our national spirituality, the work to be done in the future.